Effects of running in place accompanied by abdominal drawing-in on gait characteristics of healthy adults - Cho, Misuk (Journal of Physical Therapy Science, 2015)
[Purpose] This study was conducted to investigate the effects of running in place accompanied by abdominal drawing-in on the gait characteristics of healthy adults. [Subjects] The total number of subjects was 30, and 15 were randomly placed in the training group (TG) and 15 in the control group (CG). [Methods] To determine the gait characteristics of TG and CG, step length difference (SLD), stance phase difference (STPD), swing phase difference (SWPD), single support difference (SSD), and step time difference (STD) were evaluated using OptoGait, a gait analysis system. [Results] When the pre-intervention and post-intervention results of TG and CG were compared, statistically significant differences in SLD, SWPD, SSD, and STD of TG were found. [Conclusion] Running in place accompanied by abdominal drawing-in might help reduce the deviation between left and right gait variables during walking.